The organicity of newcomer teachers who have a major in Education for the Countryside: a construction in progress - Brenda Santos de Sousa (Universidade Federal do Tocantins, 2021)
This essay aims to present an experience report on the self-organization strategies of teachers who have a major in Education for the countryside in the Federal University of Recôncavo da Bahia. Thus, we carried out a bibliographical review of the preeminent academic references in the Rural Education for the countryside that study newcomer teacher. Additionally, we articulate the outcome of this research evidence with our own experiences. So, we framed our study by the living-and-writing (escrevivências) approach, a term coined by Conceição Evaristo. As a result, we highlight the importance to overcome the challenges faced by newcomer teacher in a counter-hegemonic course the search defends the need for permanent articulation, expanding and strengthening the network of people that constitute the Education for the countryside.